Heat shrink formation of a corrugated thin film thermoelectric generator. (October 2015) - Sun, Tianlei; Peavey, Jennifer L.; David Shelby, M.; Ferguson, Scott; O'Connor, Brendan T.
Graphical abstract: Highlights: Demonstrate and characterize a thermoelectric generator with a corrugated geometry. Employ a novel heat shrink fabrication approach compatible with low-cost processing. Use thermal impedance modeling to explore design potential. Corrugated design shown to be advantageous for low heat-flux density applications. Abstract: A thin film thermoelectric (TE) generator with a corrugated architecture is demonstrated formed using a heat-shrink fabrication approach. Fabrication of the corrugated TE structure consists of depositing thin film thermoelectric elements onto a planar non-shrink polyimide substrate that is then sandwiched between two uniaxial stretch-oriented co-polyester (PET) films. The heat shrink PET films are adhered to the polyimide in select locations, such that when the structure is placed in a high temperature environment, the outer films shrink resulting in a corrugated core film and thermoelectric elements spanning between the outer PET films. The module has a cross-plane heat transfer architecture similar to a conventional bulk TE module, but with heat transfer in the plane of the thin film thermoelectric elements, which assists in maintaining a significant temperature difference across the thermoelectric junctions. In this demonstration, Ag and Ni films are used as the thermoelectric elements and a Seebeck coefficient of 14 μV K −1 is measured with a maximum power output of 0.22 nW per couple at a temperature difference of 7.0 K. We then theoretically consider the performance of this device architecture with high performance thermoelectric materials in the heat sink limited regime. The results show that the heat-shrink approach is a simple fabrication method that may be advantageous in large-area, low power density applications. The fabrication method is also compatible with simple geometric modification to achieve various form factors and power densities to customize the TE generator for a range of applications.